Untargeted profiling of field cultivated bush tea (Athrixia phylicoides DC.) based on metabolite analysis - Cecilia, Mohale K.; Abrha, Assress H.; Hlengilizwe, Nyoni; Hintsa, Araya T.; Umer, Muhammad; Nixwell, Mudau F.; Ali, Shinawar Waseem; Afzal, Muhammad Inam; Martorell, Miquel; Salehi, Bahare; Setzer, William N.; Sattar, Muhammad Umair; et al. (Cellular and Molecular Biology, 2020)
Bush tea (Athrixia phylicoides DC.) is an aromatic South African indigenous plant used for many decades as a health beverage and medicine. Several studies have extensively investigated wild bush tea's secondary metabolites, but the entire profiling of cultivated bush tea's metabolites is limited in the literature. Thus, the objective of this study was to profile cultivated bush tea metabolites using liquid chromatography-quadrupole time of flight-tandem mass spectrometry (LC-QTOF-MS). The 31 metabolites profiled included; benjaminamide, chlorogenate, chrysosplenetin, coumarin, 6Z-docosenamide, naringenin 7-O-Î²-d-glucoside, 5-p-coumaroylquinic acid, integrastatin A, luteolin 7-O-(6-O-malonyl-Î²-d-glucoside), 1,3-dicaffeoylquinic acid, magnoshinin, okanin, (2S)-5-hydroxy-7-methoxy-6,8-dimethylflavanone, (9Z,12Z,15Z)-octadecatrienoic acid, 2"³-deamino-2"³-hydroxy-6"³-dehydroparomamine, O-butanoylcarnitine, myricitrin, gorlic acid, tetracenomycin X, sakuranin, d-tryptophan, linoleamide, laricitrin 7-monoglucoside, l-Î²-phenylalanine, l-proline, pheophytin A, pheophorbide A, PI(18:0/20:4(8Z,11Z,14Z,17Z), stearidonic acid, and gibberellin A14 aldehyde. These annotated metabolites included phenolics, flavonoids, and quinic acids, indicating that bush tea is rich in metabolites, which have a potential wide range of health benefits.